2012
DOI: 10.1108/02634501211211948
|View full text |Cite
|
Sign up to set email alerts
|

Do family SME managers value marketing capabilities' contribution to firm performance?

Abstract: Purpose -This paper seeks to extend knowledge on the impact of different marketing capabilities on various measures of organisational performance in the context of family-run small to medium-sized enterprises (SMEs). Design/methodology/approach -Aspects regarding marketing capabilities in family-owned SMEs and their impact on superior performance are identified and briefly discussed according to the existing literature. Then, quantitative research is presented followed by a discussion of the findings. The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 92 publications
2
27
2
2
Order By: Relevance
“…Given this weak relationship between "product differentiation" and "perceived financial performance," one could claim that the findings of the current study are somewhat in line with Pérez-Cabañero et al (2012) who found no significant relationship between product differentiation and financial performance of family businesses. According to them, adopting a product differentiation had no direct effect on the financial performance of family businesses.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 68%
See 3 more Smart Citations
“…Given this weak relationship between "product differentiation" and "perceived financial performance," one could claim that the findings of the current study are somewhat in line with Pérez-Cabañero et al (2012) who found no significant relationship between product differentiation and financial performance of family businesses. According to them, adopting a product differentiation had no direct effect on the financial performance of family businesses.…”
Section: Discussion and Managerial Implicationssupporting
confidence: 68%
“…In contrast to other studies, they found that product differentiation did not directly influence the financial performance of family SMEs, but instead product differentiation directly influences the non-financial performance of these businesses (Pérez-Cabañero et al 2012). Their study found that product differentiation directly contributes to stakeholder satisfaction, which in turn positively influences financial performance.…”
Section: Product Differentiation and Perceived Financial Performancecontrasting
confidence: 69%
See 2 more Smart Citations
“…For example, approximately 99% of all European businesses are SMEs, with nine out of ten being micro-enterprises employing fewer than ten people (Pérez-Cabañero, González-Cruz, & Cruz-Ross, 2012). Marketing in SMEs tends to focus on the needs of the business, so they a lack planned and controlled promotional activities, leading to assumption that marketing in SMEs is simplistic, spontaneous, informal, reactive, haphazard, and built to correspond with industry values (Fuller, 1994;Parry, Jones, Rowley, & Kupiec-Teahan, 2012;Reijonen, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%